Analisis 1 Samuel 14:52-15:3 Sebuah Pendekatan Aksen Ibrani dan Sintaks - Chia, Philip Suciadi (Jurnal Teologi dan Pelayanan Kerusso, 2024)
In the book of 1 Samuel, the selection of Saul as king of Israel is influenced by a complex historical and theological context. 1 Samuel 14:52 highlights Saul's reliance on his soldiers in battling the Philistines, which forms the background of his leadership. Conversely, 1 Samuel 15:1-3 underscores Saul's disobedience to God's command, leading to his rejection as king. This study analyzes both aspects Saul's leadership background and his disobedience using Hebrew accent and syntax methodology to explore the theological implications. The Hebrew accent methodology aids in exploring the linguistic emphasis within the text, while Hebrew syntax examines the sentence structure that provides insights into Saul’s character. The analysis reveals that although Saul experienced notable military success, his disobedience to God’s commands was the primary factor in his downfall. There is a clear connection between Saul’s reliance on human strength and his inability to fully submit to God's will. The study concludes that Saul’s rejection was not solely due to disobedience but also reflected a lack of trust in God. These findings are relevant in theological and leadership studies, emphasizing the importance of obedience to God and warning contemporary leaders of the dangers of relying on human strength.